Perancangan Sistem Pengendalian Kualitas di PT X - Puspitasari, Ellen Yunita; Yang Aysia, Debora Anne (Jurnal Titra, 2015)
PT X is a private company, which is manufacturing security and safety protection. There is no quality control system on production process, which cause 100% rework. Quality control system has been design to control the incoming material, production process, and finish goods. Quality control system design done by creating quality characteristics, cheek sheets, and work instructions. Which is obtained by directly observing at production process, and interview with the members of company. Suggested quality control system has been verified by the company and can be seen in the quality plan.Â